Multi-omic analysis of precocious puberty girls: pathway changes and metabolite validation - Zhou, Fang; Mao, Jianhong; Jin, Zhenzhen; Zhu, Li; Li, Xiaofang (Frontiers in Endocrinology, 2024)
Objective Precocious puberty (PP) is a prevalent endocrine disorder affecting the physical and mental wellbeing of children. Identifying the triggering factors of PP has become a central issue. This study seeks to investigate the metabolomic and transcriptomic alterations in PP. Material and methods First, 37 school-aged girls diagnosed with PP and 25 age-matched prepubertal control girls were recruited, and the fecal samples were collected for non-targeted metabolomic analysis to screen for differentially expressed metabolites (DEMs). Subsequently, an animal model of PP was constructed by danazol administration to neonatal female rats, and both fecal non-targeted metabolomics and serum next-generation transcriptomic sequencing were performed to screen DEMs and differentially expressed genes (DEGs) in PP. Moreover, the DEM co-existing in clinical and animal models was administrated to PP rats to explore the role of the target metabolite in PP. Results A total of 24 DEMs in PP clinical samples and 180 DEMs and 425 DEGs in PP animal samples were identified. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that these DEMs and DEGs were enriched in disease-associated pathways, including fatty acid synthesis, glycerolipid metabolism, pyrimidine metabolism, steroid hormone biosynthesis, progesterone-mediated oocyte maturation, and gonadotropin-releasing hormone (GnRH) signaling pathway, forming a tight DEM–DEG pathway regulatory network. Further DEM validation demonstrated that thymine supplementation delayed the opening of the vagina and development of PP in model rats. Conclusion This study reveals that the metabolomic and transcriptomic changes, along with enriched pathways, are implicated in PP based on clinical and animal analyses. The findings may provide new strategies and research avenues for PP treatment.